You are viewing a single comment's thread. Return to all comments →
f :: Int -> [Int] -> [Int] f n [] = [] f n (x:xs) = (helper (n) (x:xs)) ++ f (n) xs where helper n (x:xs) | n==0 = [] | otherwise = x:helper (n-1) (x:xs)
Haskell beginner here
Seems like cookies are disabled on this browser, please enable them to open this website
An unexpected error occurred. Please try reloading the page. If problem persists, please contact support@hackerrank.com
List Replication
You are viewing a single comment's thread. Return to all comments →
Haskell beginner here